Osteofibrous Dysplasia with Rhabdoid Elements in a 38-Year-Old Man with Spontaneous Regression Over Five Years: A Case Report. Issue 3 (July 2018) - Exner, G. Ulrich; von Hochstetter, Arthur R.; Pfirrmann, Christian W.A.
Abstract : Case: A 38-year-old man presented with multifocal, partially confluent osteolytic lesions in the proximal dia-meta-epiphyseal region of the proximal aspect of the left tibia, which had been found incidentally when a radiograph was made after a rotational knee injury. When the results of a percutaneous core needle biopsy proved inconclusive, an open biopsy was performed. Osteofibrous dysplasia (OFD) with scattered groups of plump cells with a rhabdoid phenotype, shown to express both vimentin and pan-cytokeratin, was found. Because the lesion was an incidental finding, we decided to proceed with observation. Three months after the open biopsy, imaging showed marked regression of the lesion; there was nearly complete normalization 5 years later. Conclusion: To our knowledge, there has been only 1 prior reported case with these pathologic features, and there have been no reports of complete spontaneous regression in an adult patient with OFD. Treatment recommendations for OFD and for OFD-like adamantinoma range from observation to aggressive resection.